Pelatihan Perakitan Komputer Untuk Meningkatkan Keterampilan Bagi Santri di Ponpes Al Mutmainnah - Valian Yoga Pudya Ardhana; M. Dermawan Mulyodiputro (Puslitbang Akademi Relawan TIK Indonesia (ARTIKA), 2023)
The role of computers in everyday life is increasingly important. Computers can be used as a tool for running a business and doing all office, industrial, construction and lecture tasks. Computers have many varieties of both types and types, ranging from standard types, medium to high-tech computers. With the large role of computers at this time, the Al Mutmainnah Islamic Boarding School in the Kediri sub-district, West Lombok Regency, collaborated with the community service team at Qamarul Huda Badaruddin University to provide computer assembly training to students. This training is intended to equip students to have special skills in computer assembly and later it is hoped that they will be able to open their own jobs from this computer assembly training. The material provided can be received, digested, and understood by the participants well. The large number of participants in proportion to the number of devotees made this training more conducive. The activity went smoothly, on time and as expected and the students were able to communicate well with the speakers and other students.